Lateral pressure on piles in ground undergoing horizontal movement - Ong, Chee Seng. (2008)
A large scale model test rig was built to investigate the lateral soil pressure acting on a pile in sand when it is subjected to horizontal soil movement. A total of 42 model tests were conducted. Both single pile and 2-pile tests were carried out under different sand densities, soil movement profile and surcharge load.